Humanizing Technology : Rekonstruksi Pendidikan Akhlak di Tengah Hegemoni Algoritma Era Society 5.0 - Nur Khairani; Tiana Atika; Herlini Puspika Sari (Fakultas Pendidikan Islam dan Keguruan Universitas Garut, 2026)
This research is motivated by the phenomenon of algorithmic hegemony in the Society 5.0 era, which has the potential to erode human values and the moral integrity of students. The aim of this research is to formulate a reconstruction of moral education as an effort toward